TDD-CDMA for wireless communications - Esmailzadeh, Riaz (Artech House universal personal communications series., 2003)
Look to this cutting-edge new resource for a comprehensive description of TDD-CDMA technology. The book provides you with in-depth coverage of the important TDD-based standards, including the 3GPP's TD-CDMA for UMTS, and TD-SCDMA, the Chinese 3G standard. You gain a thorough understanding of the differences between the TDD and FDD modes of CDMA, and discover the advantages of TD-CDMA and TD-SCDMA in 3G systems. What's more, you find keen insight into the future research directions and prospects for 4G networks.